Coverage, positiveness and incidence in neonatal inquiry of congenital hypothyroidism in the Cienfuegos Province. 2012-2016 - María de Jesús Sánchez Bouza; Julia Surí González; Isabel Vega Bolaños; Regla Balmaseda Rangel; Ana Esther Benavides Sureda; Pedro Sánchez Frenes (Medisur, 2018)
Foundation: in Cuba, where health is conceived as a main component of quality of life, a program for early detection of congenital hypothyroidism is developed. This is the most endocrine disease in this period of life which is the most common cause of preventive mental retardation. Objective: to characterize the positiveness of the first trial, the incidence of the disease and the coverage of the Inquiry Neonatal Program of Congenital Hypothyroidism in the Cienfuegos Province. Methods: retrospective descriptive study which included all newborns in Cienfuegos from 2012 to 2016. A sanitary documentary review was done. The inquiry results were taken into consideration the number of studied alive newborns (coverage), the positive cases in the first determination (positiveness) and the confirmed ones (incidence), according to the geographical areas of the province and years expressed in percentages and rates. Results: a 100% of coverage was achieved for the study. A heterogeneous distribution was observed of the positive results of the first laboratory determination and the confirmation in some territories. The incidence rate of congenital hypothyroidism was 0, 23 for every 1000 born alive, all from the female sex. Conclusion: the results show the success of the Inquiry Program in the province which may be improved in some aspects mainly in pre-analytical stage of the laboratory trials to maintain its results and achieve better ones.